Treatment of depression and anxiety in Parkinson’s Disease - Troeung, Lakkhina (Curtin University, 2013)
This thesis examined the treatment of depression and anxiety in Parkinson’s disease (PD) and comprised four studies. Study 1 was a meta-analysis of treatments for depression and anxiety in PD. Study 2 examined the validity of the DASS-21 as an assessment tool in PD. Study 3 was a randomised controlled trial of group CBT for depression and anxiety in PD. Study 4 was a cross-sectional cohort study examining mental health service utilisation and barriers to treatment.